2012
DOI: 10.1021/la300009a
|View full text |Cite
|
Sign up to set email alerts
|

Near Field Guided Chemical Nanopatterning

Abstract: This article demonstrates the possibility of creating well-defined and functional surface chemical nanopatterns using the optical near field of metal nanostructures and a photosensitive organic layer. The intensity distribution of the near field controlled the site and the extent of the photochemical reaction at the surface. The resulting pattern was used to guide the controlled assembly of colloids with a complementary surface functionality onto the substrate. Gold colloids of 20 nm diameter were covalently b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Strategy for near fi eld guided chemical nanopatterning followed by nanoparticle assembly (A). [ 72 ] The intensity distribution of the near fi eld controls the site and the extent of the two-photon cleavage of the nitroveratryl group at the surface. Upon cleavage, an amine functional group was released, which was used to site-selectively bind species with complementary chemical functionality on the surface.…”
Section: Multifunctionality Based On Wavelengthselective Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Strategy for near fi eld guided chemical nanopatterning followed by nanoparticle assembly (A). [ 72 ] The intensity distribution of the near fi eld controls the site and the extent of the two-photon cleavage of the nitroveratryl group at the surface. Upon cleavage, an amine functional group was released, which was used to site-selectively bind species with complementary chemical functionality on the surface.…”
Section: Multifunctionality Based On Wavelengthselective Responsementioning
confidence: 99%
“…Reproduced with permission. [ 72 ] and used in a similar manner for assembling target proteins (Figure 7 ). [ 83 ] It is important to note that proteins can interact with surfaces via multiple different interactions due to their complex structure.…”
Section: Multifunctionality Based On Wavelengthselective Responsementioning
confidence: 99%
“…These LSP can concentrate the electric field at the surface of nanostructures to very small spots ‐ the hotspots ‐ which can then serve as miniature molecular reactors. Within such hotspots, photochemical reactions,3 chemical transformations,4 and catalytic reactions can take place 5, 6. These processes are facilitated by the large amplitude of the local electric fields that can give rise to impressive signal enhancements, as in the case of Raman scattering,7 which can be increased up to fourteen orders of magnitude 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, active molecules should be confined within the plasmonic hot spots to maximize the plasmon-molecule coupling. It has been shown that selective functionalization with plasmon-activated photochemistry can be employed to achieve the site-selective control of molecules [123].…”
Section: Theoretical Analysismentioning
confidence: 99%